Tattoos as body text and tribal identity: a study of Sirawon Tulisen Khating’s “retold by Grandma-Yarla’s Tattoos” and Nidhi Dugar Kundalia’s “The Godna Artists of Jharkhand” - Sachdeva, Saru; Rani, Rekha (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tattoos are important markers of tribal cultural identity. As embodied texts, they not only reflect a worldview but also become repositories of historical and ontological memory. As carriers of traditions, customs, and beliefs, they manifest the collective identity of the people and guide and bind them as a community. As such, tattooing or godna acquires a much wider significance than being a mere bodily art. It turns into an aesthetic-narrative entry point into tribal consciousness, cultural worldview, identity and history. In their engagement with their identity, the tribal writers dig deep into their cultural repository to foreground the truth of their being and becoming. In the present paper, an attempt is made to understand the nature of this tribal negotiation of 'tattooing' as a textual metaphorical tradition through a critical study of Sirawon Tulisen Khating’s “Retold by Grandma-Yarla’s Tattoos” and Nidhi Dugar Kundalia’s “The Godna Artists of Jharkhand". The paper uses the insights from Raymond Williams's cultural theory to deconstruct and critically analyse the tribal practice of tattooing and its relational dynamics within the tribal society. Using memory as a trope and the concept of collective theory as a theoretical framework, the paper sets out to see how gender and caste/class notions are upheld during the tattooing process. Looking through the tattoo as a significant cultural practice in the tribal world, the paper also exposes the diverse class and caste hierarchies prevalent among tribals.